Catalytic activity of nickel(II) oxide nanoparticle-[C60]fullerene nanowhisker composite for reduction of 4-nitroaniline. Issue 8 (2nd August 2020) - Ko, Jeong Won; Jeon, Sugyeong; Ko, Weon Bae
Abstract: Nickel(II) oxide nanoparticles were prepared using the sol-gel method. Subsequently, a nickel(II) oxide nanoparticle-[C60 ]fullerene nanowhisker composite was synthesized using the nickel oxide(II) nanoparticle dispersion, C60 -saturated toluene, and isopropyl alcohol via the liquid-liquid interfacial precipitation (LLIP) method. The resulting composite was characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman spectroscopy, and transmission electron microscopy (TEM). The catalytic activity of the nickel(II) oxide nanoparticle-[C60 ] fullerene nanowhisker composite for 4-nitroaniline reduction was evaluated with ultraviolet-visible (UV-vis) spectroscopy. The kinetic study confirmed that the reduction of 4-nitroaniline using the hybrid nanocomposite followed a pseudo-first order reaction.